Toward Evidence-Based Practice. Issue 4 (July 2022) - Rohan, Annie; Breman, Rachel Blankstein; O'Brien-Abel, Nancy; Roth, Cheryl K.
Abstract : Experts suggest how 6 research articles can be used in nursing practice.